HIGH-RISK INTERNET ADDICTION IN ADOLESCENTS DURING PANDEMIC COVID-19 AND PARENTS’ ROLE - Ayu Putri; Yunias Setiawati; Yi-Ting Shieh; Sih-Hsien Lin (Jurnal Berkala Epidemiologi, 2022)
Background: The use of smartphones among adolescents has been increasing during the COVID-19 pandemic, especially using the internet daily, because adolescents do not have physical activities during the lockdown. Using the internet for doing assignments from school, using social media as a substitute for meeting with their friends directly, introducing new people and the internet for entertainment such as playing the game online, listening to music or watching a film. Purpose: This literature aimed to study the risk of internet addiction in adolescents during the COVID-19 pandemic and know parents’ role to accompany adolescents while using the internet daily. Methods: A review of articles on internet use in adolescents during the pandemic was done to determine the risk of internet addiction. This article included article review, systematic review, research journals, qualitative and quantitative methods, and books. Meanwhile, the exclusion journals were not in English. The search of journals accessed from Google Scholar, Pubmed, and Science Direct with keywords ‘adolescents’, ‘internet addiction’, ‘parenting’, ‘education’ and ‘COVID-19’. Results: Internet use has been increasing during the COVID-19 pandemic and is at risk of causing addiction to adolescents. Unattended use of the internet and time restrictions from parents are at risk of causing internet addiction in adolescents. Conclusion: Internet use has been increasing during the COVID-19 pandemic and is at risk of causing addiction in adolescents. Time restriction and parental supervision are needed for adolescents to use the internet daily.